Pengaruh diameter sudu terhadap kinerja turbin angin berporos horizontal - Rudiyanto, Rudiyanto; Budiyanto, Eko; Kurniawan, Rubi; Sumosusilo, Joko (Universitas Muhammadiyah Metro, 2020)
Fossil energy is a limited and non-renewable source of energy, therefore it is necessary to look for alternative energy solutions that are not available and can be updated. Another reason is to reduce the impact of pollution caused by the use of fossil energy. As we all know, the biggest source of pollution in the world comes from exhaust gas/fossil fuel emissions. These plants can convert wind energy into electrical energy using wind turbines or windmill. The electricity generation system using wind as an energy source is an alternative system that is very rapidly developing, considering that wind is an energy that is not limited in nature. The purpose of this study was tested using three blades, varying the diameter with a slope of 150, namely to determine the effect of blade diameter on the power produced by the turbine and the efficiency of the horizontal shaft wind turbine. The turbine power testing method is done manually by using 2 spring balance which is associated with the belt, v-belt, then the v-belt is associated with an 8 cm diameter pulley that is on the turbine shaft, the friction between the belt and the pulley is ignored. From the test results, the torque produced by the turbine is carried out in a certain rotation. Wind turbines made with blade blades 2 m, 2.40 m, 2.80 m with wind speeds of 4 m / s From the three turbine blade variables based on testing different turbine blade diameter the resulting power is different, from the test results it can be known the power generated by the power turbine can be seen that the highest power on the blade diameter is 2.40 m at 140 turns (rpm) with turbine power of 19.9606 watts, with an efficiency of 10,6263 % and the lowest in blade diameter 2m in rotation 120 ( rpm) with turbine power of 12.9374 watts, with an efficiency of 9,9579 %.